TINJAUAN RANTAI PASOK KOMODITI KELAPA DI PT. BONTOJALLING BAOJI INDONESIA - M. Dakhri Sanusi (Jurnal Bisnis dan Kewirausahaan, 2019)
The objective of this scientific paper is to figure out the supply chain of coconut commodity at PT. Bontojalling Baoji Indonesia, knowing the constraints experienced in the supply chain of coconut commodity. The scientific paper used qualitative descriptive, to describe the result of observation and data analysis at field observation which was taken on February to April 2018. Having analyzed and discussed problem generalization, the writer concluded that supply chain of coconut commodity supply at PT Bontojalling Baoji Indonesia, starting from coconut farmers, coconut collectors, coconut suppliers, coconut storage warehouse and export. As well as the contraints faced are increased implementation costs, undefined performance measurements, inefficient information systems, inaccurate and often late delivery of status data, inventory policies are too simple, discrimination against internal customers, coordination between supply activities, production and poor delivery, declining quality levels, conflicts and disputes and lack of commitment among suppliers, resulting in the delay in the arrival of raw materials in the company’s storage warehouse which resulted in hampered export action.